Scope for latitudinal extension of reef corals is species specific - Joshua Madin; Andrew Allen; Andrew Baird; John Pandolfi; Brigitte Sommer (Frontiers of Biogeography)
In their recent paper, Muir et al. (Science, 2015, 348, 1135-1138) demonstrate that the maximum depths of staghorn coral assemblages are shallower at higher latitudes, a trend that correlates with winter light levels. Based on these findings, the authors hypothesize that light availability limits the current latitudinal extent of the group and will constrain future range expansion. Here we reanalyze their data and show that depth-latitude relationships vary substantially among species, and that most species show either no significant pattern or the opposite pattern. In so doing, our reanalysis highlights a common misinterpretation of mixed-effects models: the fallacy of the average. Our findings are also consistent with fossil and contemporary observations of coral range-shifts. The factors that limit the current range extent of corals remain elusive, but they are likely species-specific and will require much further research to elucidate.